Understanding the Educational Psychology and English Language Teaching: Insights for both EFL and Non-EFL Learners - Fitria, Tira Nur (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
This library research describes the importance of understanding Educational Psychology and English Language Teaching (ELT) to EFL and non-EFL students. Educational psychology is a vital skill for educators to effectively teach students, as it helps them understand their personality, thinking patterns, learning readiness, motivation, emotional state, and difficulties in learning English such as reading, writing, listening, and speaking skills. English teachers can utilise this understanding to design the lesson plan, handle classroom management, and offer guidance and counselling for students. English teachers/lecturers should set learning objectives, choose appropriate strategies, and foster a positive learning environment. Thus, mastering educational psychology helps English language teachers and lecturers to overcome learning problems and foster a conducive environment in the classroom. Further, studying educational psychology offers numerous benefits for English teachers/lecturers and prospective English teachers/lecturers, such as understanding individual differences, creating conducive learning environments, choosing the right learning strategy, providing guidance, and motivating learners. They must be aware of their students' personalities and preferences to create effective learning. Equally significant, educational psychology contributes to curriculum design, the learning system, and assessment systems, helping English teachers/lecturers understand the unique needs and abilities of students and guide academic problems.